Разработка мероприятий по снижению рисков при эксплуатации линий электропередач - Гусельников М. Э. Михаил Эдуардович; Гуляев М. В. Милий Всеволодович; Сечин А. И. Александр Иванович; Сечин А. А. Андрей Александрович; Романцов И. И. Игорь Иванович; Авдеева И. И. Ирина Ивановна; Давлатов Л. Д. (Промышленная безопасность, 2022)
Заглавие с экрана